Corporate governance and capital safety at Vietnamese joint stock commercial banks - Doan, Ha Thanh; Le, Anh Hoang; Doan, Thu (The Economics and Finance Letters, 2025)
This study evaluates the capital adequacy ratio (CAR) of Vietnamese commercial banks. Simultaneously, we assessed the impact of corporate governance on the capital adequacy ratio of Vietnamese joint stock commercial banks. We used SGMM and Bayesian methods to estimate models employing data from 28 Vietnamese commercial banks between 2012 and 2023. The findings indicated that variables including previous period CAR, deposit ratio, loan loss reserve, economic growth, board size, the share of female board members and educational qualifications significantly enhance the CAR of Vietnamese commercial banks. On the other hand, CAR exhibits a negative and statistically significant correlation with bank profitability, size, leverage ratio, non-performing loans, and CPI. We have recommended many policy implications to safeguard capital inside the Vietnamese commercial banking sector based on research findings.